2008
DOI: 10.1007/s10336-008-0316-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Black-tailed Godwit Limosa limosa: substructuring revealed by mtDNA control region sequences

Abstract: Black-tailed (Limosa limosa) and Hudsonian Godwits (L. haemastica) are sometimes described as a superspecies. The Black-tailed Godwit is further split into three subspecies on the basis of morphological differences (L. l. limosa, L. l. islandica and L. l. melanuroides). We studied variation in partial mtDNA control region sequences among Black-tailed and Hudsonian Godwits which showed 5% divergence. Black-tailed and Hudsonian Godwits were thus clearly differentiated and the separate species status for the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…The level of genetic diversity in the Black-tailed Godwit in our study is higher (average of 6.3 alleles per locus) compared to that reported by Höglund et al (2009) who found rather low genetic diversity (1 haplotype) within Dutch Black-tailed Godwits using mitochondrial DNA. However, the marker they used (the second domain of the control region, a part that is highly conserved) might be less suitable for detection of genetic variation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The level of genetic diversity in the Black-tailed Godwit in our study is higher (average of 6.3 alleles per locus) compared to that reported by Höglund et al (2009) who found rather low genetic diversity (1 haplotype) within Dutch Black-tailed Godwits using mitochondrial DNA. However, the marker they used (the second domain of the control region, a part that is highly conserved) might be less suitable for detection of genetic variation.…”
Section: Discussioncontrasting
confidence: 53%
“…Subsequently, AMOVA showed that more than 99% of the molecular variation was found across all individuals, while an insignificant proportion (0.3%) was attributable to variation between individuals from different locations. Interestingly, Höglund et al (2009), using mitochondrial DNA from four Dutch Black-tailed Godwit breeding sites, did not detect any genetic structure either. This suggests that all subpopulations are affected by long term panmixis or that gene flow between different breeding areas ceased too recently for both marker types to detect geographical differences (Zink and Barrowclough 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Long-distance migratory shorebirds include species with deeply diverged subspecific lineages that apparently survived the LGM in distinct populations, such as Dunlin C. alpina (Buehler and Baker 2005;Wenink et al 1993) and Black-tailed Godwit Limosa limosa (Höglund et al 2009;Trimbos et al 2014), and also those which presumably underwent bottlenecks in one or few LGM refugia and only (Wenink et al 1994). In mtDNA, the latter group are distinguishable by lower sequence variation and shallow divergences (i.e., star-like networks with haplotypes differing by only single base-pair changes).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used material to investigate genetic population structure in birds are blood samples (Coulon et al 2008;Hoglund et al 2009;Larsson et al 2008;Manier and Arnold 2005;Milot et al 2008;Ortego et al 2008;Ottvall et al 2005). Obtaining blood samples is somewhat invasive, and in many countries only certified observers are allowed to sample blood.…”
Section: Introductionmentioning
confidence: 99%